2006
DOI: 10.1021/jf0607157
|View full text |Cite
|
Sign up to set email alerts
|

From Field to Health:  A Simple Way To Increase the Nutraceutical Content of Grape As Shown by NO-Dependent Vascular Relaxation

Abstract: Polyphenolic grapevine components involved in plant resistance against pathogens possess various pharmacological properties that include nitric oxide (NO)-dependent vasodilation and anti-inflammatory and free radical scavenging activities, which may explain the protective effect of moderate red wine consumption against cardiovascular disease. The aim of this work was (a) to verify the possibility that preharvest treatments of grapevine with a plant activator, benzo-(1,2,3)-thiadiazole-7-carbothioic acid S-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
(23 reference statements)
0
39
0
1
Order By: Relevance
“…Field treatments of grapevine with BTH improve resistance to B. cinerea and enhance resveratrol and anthocyanin biosynthesis [68]. Similar studies also found an increase in total polyphenols in berry skin, particularly, the proanthocyanidin fraction [44,69], and in the anthocyanin, flavonol, and proanthocyanidin content of grapes and the color of the corresponding wines [70]. Postharvest treatment with BTH resulted in an enhancement of the phenolic and anthocyanin contents of strawberries [71].…”
Section: Mejmentioning
confidence: 71%
“…Field treatments of grapevine with BTH improve resistance to B. cinerea and enhance resveratrol and anthocyanin biosynthesis [68]. Similar studies also found an increase in total polyphenols in berry skin, particularly, the proanthocyanidin fraction [44,69], and in the anthocyanin, flavonol, and proanthocyanidin content of grapes and the color of the corresponding wines [70]. Postharvest treatment with BTH resulted in an enhancement of the phenolic and anthocyanin contents of strawberries [71].…”
Section: Mejmentioning
confidence: 71%
“…In grapes, the higher phenolic content was linked to the enhanced resistance against Botrytis cinerea in the fruits (10). Preharvest BTH treatment has also given protection against postharvest gray mold in strawberries (15), suggesting that BTH causes long-term changes in secondary metabolism, which might not only improve resistance to pathogens but also influence the nutritional value and bioactive properties of the crop (22). Concentration of Salicylic Acid.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, few studies have been conducted on the changes of secondary metabolites in edible plant parts in any crop species after BTH treatment, although it might have an influence on the nutritional quality of the crop (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports in the literature have linked the moderate consumption of products such as wine and grape juices with a reduced incidence of coronary heart disease [2], prevention of Among the various phenolic antioxidants present in grapes, (+)-catechin, (−)-epicatechin, resveratrol, quercetin and its glucosides (Figure1) are the most potent, since they have been found to protect the human LDL against oxidation more efficiently than α-tocopherol on a molar basis [12]. They are also active as potent promoters of vascular relaxation through the generation of nitric oxide by the endothelium [13]. In addition, trans-resveratrol and quercetin are potent inhibitors of platelet aggregation in rats [14] and modulate eicosanoid synthesis toward a pattern likely to be protective against CHD [15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are many reports in the literature concerning the resveratrol isomers and glycosides [19] content of various wine samples and some research, including our own [20], on the concentration of other biologically interesting polyphenolic antioxidants, such as flavonoids (eg. (+)-catechin, (-)-epicatechin [13,21]. On the other hand, investigations on the concentration of polyphenolic antioxidants in grapes concern mostly the assay of grape berries during different stages of their maturation or when they have been injured by disease or UV irradiation [22,23].…”
Section: Introductionmentioning
confidence: 99%